Association of globulin concentrations with prognosis in horses with lymphoma - Wensley, Fiona M.; Berryhill, Emily H.; Magdesian, K. Gary (Frontiers in Veterinary Science, 2023)
Lymphoma is the most common hemopoietic neoplasia in horses. Common clinicopathologic abnormalities in equine lymphoma include hyperglobulinemia, hypoalbuminemia, hyperfibrinogenemia, anemia, thrombocytopenia and lymphocytosis. Hypoglobulinemia has been reported in other species with lymphoma, however it has not been well described in horses. The objectives of this study were to examine the prevalence of hypoglobulinemia in equine lymphoma, and to identify prognosis and clinicopathological abnormalities associated with serum globulin concentrations. Ninety-six horses with lymphoma were investigated in this retrospective study. Patients were allocated into groups based on serum globulin concentration. Survival analysis was performed to determine risk factors associated with globulin concentration and outcome. Nineteen horses were hypoglobulinemic (2.1g/dL), 63/98 were normoglobulinemic (2.2-4.3g/dL), and 16/98 were hyperglobulinemic (4.4g/dL). Hyperglobulinemia was associated with a higher anion gap (P = 0.0005), lower bicarbonate (P = 0.006), sodium (P = 0.03) and chloride concentrations (P = 0.002), and higher total protein than hypoglobulinemic horses (P < 0.0001). For location, 37% of horses with mucocutaneous lymphoma were hypoglobulinemic, compared to none in the hyperglobulinemic group (P = 0.02). Survival times were significantly different between low, normal and high globulin groups (P = 0.0002, median [range] survival times: 333 [1-3792], 43 [1-4001] and 4 [1-129] days, respectively). Significant risk factors for shortened time to death were hyperglobulinemia (HR 2.4, P = 0.02), T cell lymphoma (HR 3.5, P < 0.0001), and multicentric (HR 3.1, P = 0.0008) and mediastinal (HR 6.4, P = 0.006) forms of lymphoma. Lack of chemotherapy was associated with shortened survival time (HR 4.5, P < 0.0001). B cell lymphomas (P < 0.0001) and mucocutaneous lymphoma location (P < 0.0001) were associated with longer survival times. Serum globulin concentrations are associated with location of lymphoma, clinicopathologic abnormalities, and survival times in equine lymphoma.